ACTION AND EQUATIONS OF MOTION IN F(Q,B) GRAVITY WITH FERMIONIC FIELDS - Bekov , С.; Altabayeva , А.; Myrzakulov , К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
In this paper, a modified theory of gravity of a filled fermionic field of a flat and homogeneous Friedman universe is considered. The flat and homogeneous Friedman universe is one of the main cosmological models, and it agrees well with the observational data. This is because on a large scale, the universe can be considered flat, homogeneous and isotropic. The purpose of the work is to theoretically study the dynamics of the second stage (phase) of the evolution of the accelerated expansion of the Universe within the framework of the modified theory f(Q,B) of gravity. Q non-metric scalar, which mathematically describes the change in the length of the vector in the process of parallel transfer and is the main geometric variable that describes the properties of gravitational influence. The scalar B is a boundary term between the Ricci scalar R and the torsion scalar T . The equations of motion in the considered gravitational model were determined by the variational method.